Transformative Critical Education: Reinterpreting Education - Indri, Indri (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Learning is understood as the process of interpreting an experience or action based on the renewal or revision of previously owned understanding. Transformation in learning occurs in the perspective of values, frame of reference, and mindset. This paper aims to explore the concept of transformative critical education as a reinterpretation of education. This paper uses a literature study approach. The results of the study show three basic principles in transformative critical education; first, the principle of Liberalization. Second, the principle of Humanization. Third, the principle of Transcendence. The most basic thing to be used as a starting point in the design and development of transformative learning models to identify of process. The most significant process in transformative learning occurs in the communicative domain, starting from the identification of problems, values, or initial perspectives, testing assumptions, dialogue with critical discourses, to drawing conclusions based on the results of the discourse.